2010
DOI: 10.1155/2010/595692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Polymerase Chain Reaction Methods for the Rapid Detection of Human Fecal Pollution in Marine and Inland Waters

Abstract: We compared the effectiveness of three PCR protocols for the detection of Bifidobacterium adolescentis and one PCR protocol for detecting Bacteroidales as indicators of human fecal pollution in environmental samples. Quantitative PCR indicated that a higher concentration of B. adolescentis DNA was recovered from sewage samples on the 0.2 μm filters compared to the 0.45 μm filters, and there was no evidence of qPCR inhibitors in the DNA extracts. With the Matsuki method (1999), B. adolescentis was detected only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The detection of the RuBac marker at the cattle farming sites agrees with previous MST research that demonstrated that cattle are the major source of fecal pollution in this region of the Oconee watershed [8,19,28]. Even though we did not observe cross reaction between the HuBac primers and cattle fecal DNA in our controls, it was still possible that the detection of the HuBac marker in some of the cattle farming sites could be attributed to the tendency of this PCR assay to cross react with cattle fecal samples [15,29]. This reasoning is supported by the fact that there were no houses in close proximity to the cattle farms in the watershed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The detection of the RuBac marker at the cattle farming sites agrees with previous MST research that demonstrated that cattle are the major source of fecal pollution in this region of the Oconee watershed [8,19,28]. Even though we did not observe cross reaction between the HuBac primers and cattle fecal DNA in our controls, it was still possible that the detection of the HuBac marker in some of the cattle farming sites could be attributed to the tendency of this PCR assay to cross react with cattle fecal samples [15,29]. This reasoning is supported by the fact that there were no houses in close proximity to the cattle farms in the watershed.…”
Section: Discussionsupporting
confidence: 90%
“…Environmental samples were assessed for possible PCR inhibition by amending with Bifidobacteria DNA as described by Bachoon et al 010. Changes of less than two C T value were observed, which indicates that the extracted DNA did not contain impurities that significantly inhibited the PCR (Bachoon et al 2010). The detection limit for STEC was 1.50 × 10 2 gene copies per 100 mL of water sample.…”
Section: Qpcr Setup and Controlsmentioning
confidence: 94%
“…porcinum has been proposed as an MST marker for animal species (35). Some of these Bifidobacterium markers have been successfully applied in Europe and some parts of the United States (2,8,14,21,26,38).…”
mentioning
confidence: 99%
“…In fact, the number of studies with a comprehensive temporal component is relatively small, and more importantly, most have been conducted with samples collected in temperate regions. To date, most source-tracking studies conducted in tropical waters have not comprehensively accounted for seasonal variations, have been conducted using a small number of sites, and have not evaluated the host specificity and host distribution of the assays using a significant number of fecal samples from targeted and nontargeted hosts (19,43).…”
Section: Discussionmentioning
confidence: 99%